Proses Interaksi dan Integrasi Intern Pemeluk Agama - Andi Rosadisastra (Refleksi: Jurnal Kajian Agama dan Filsafat, 2009)
This paper provides one model of research on “Anthropology of Religion”, especially related to the integration of internal conflict and religious communities that have been well demonstrated in the book: “Conflict and Integration: Different thought of Islam” by Achmad Fedyani. Fedyani find that there are five factors of religions internal conflict between the NU and Muhammadiyah, namely: problem talafuz bi al-niyyat, talqīn problems, asyrakal problems, and problems “maaruwah”. On the other side, it was found that the damping factor is the complexity of conflict and modernization; three developments of national culture, changes in the organization, awareness of the unity of traditional culture and the mixed communities.